Biomechanical evaluation of two modified intramedullary fixation system for treating unstable femoral neck fractures: A finite element analysis - Huang, Qiang; Zhang, CongMing; Bai, HuanAn; Wang, Qian; Li, Zhong; Lu, Yao; Ma, Teng (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: The existing implants for fixation of femoral neck fractures have poor biomechanical stability, so the failure rate is high. We designed two modified intramedullary implants for treating unstable femoral neck fractures (UFNFs). We tried to improve the biomechanical stability of fixation by shortening the moment and reducing stress concentration. Each modified intramedullary implant was compared with cannulated screws (CSs) through finite element analysis (FEA). Methods: Five different models were included: three cannulated screws (CSs, Model 1) in an inverted triangle configuration, the dynamic hip screw with an anti-rotation screw (DHS+AS, Model 2), the femoral neck system (FNS, Model 3), the modified intramedullary femoral neck system (IFNS, Model 4), and the modified intramedullary interlocking system (IIS, Model 5). Three-dimensional (3D) models of femur and implants were constructed by using 3D modelling software. Three load cases were simulated to assess the maximal displacement of models and fracture surface. The maximal stress at the bone and implants was also evaluated. Results: FEA data showed that Model 5 had the best performance in terms of maximum displacement while Model 1 had the worst performance for this index under axial load of 2100 N. With respect to Maximum stress, Model 4 had the best performance while Model 2 had the worst performance under axial load. The general trends under bending and torsion load were consistent with that under axial load. Our data demonstrated that the two modified intramedullary implants exhibited the best biomechanical stability, followed by FNS and DHS+AS, and then three CSs in axial, bending, and torsion load cases. Conclusion: The two modified intramedullary designs showed the best biomechanical performance among the five implants included in this study. Therefore, this might provide some new options for trauma surgeons to deal with unstable femoral neck fractures.